South Africa’s efforts to Project Influence and Power in Africa (2000 to 2017) (The Strategic Review for Southern Africa, 2020)
The article aims to explain the reasons and ways South Africa aimed to project influence and power on the African continent. It analyses the ways that SA projected influence through its foreign polices at the international and multilateral levels as well as the ways it used its military in support of its foreign policy goals. Case studies in this regard which are discussed include its involvement in Burundi, Darfur, Sudan, Libya, Democratic Republic of the Congo, the Central African Republic and South Sudan. It is concluded that South Africa remained committed to its foreign policy goals but struggled to influence international and multilateral institutions to become involved or support these goals. Lastly, it concludes that South Africa’s aim to project power in Africa was unsuccessful. Therefore, South Africa could no longer be seen as middlepower but rather as an ever-weakening State.